Trial justice the international criminal court and the Lord's Resistance Army - Allen, Tim. (London Palgrave Macmillan, 2006)
The first major case before the International Criminal Court is the appalling situation in northern Uganda where Joseph Kony's Lord's Resistance Army abducted thousands, many of them children, and systematically tortured, raped, maimed and killed them. This book argues that much of the antipathy to the ICC is based upon ignorance and misconception. Drawing on field research in Uganda, it shows that victims are much more interested in punitive international justice than has been suggested, and that the ICC has made resolution of the war more likely.
Includes bibliographical references (p. 218-222) and index.
Keywords: International Criminal Court